Evaluating the knowledge and practices of nurses and paramedics in blood transfusion services - A survey in the states of Tamil Nadu and Pondicherry, India - Raj Bharath Rudrappan (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Blood transfusion service is an important part of our healthcare system whose aim is to provide safe, effective blood components for the patient's requirement. The laboratory technicians and nurses working in the blood bank form the core for the effective functioning of blood bank. The study was to analyze the knowledge, attitude, and practice of nurses and paramedics such as laboratory technicians working in blood banks and whether intervention of a training program had any benefit to the participants. MATERIALS AND METHODS: This study was conducted in our department which is a regional training center approved by the National AIDS Control Organization for training medical officers, laboratory technicians, and staff nurses working in blood banks. There were a total number of 48 government run hospital blood banks who participated in the study and we conducted six training programs for 43 nurses and 64 laboratory technicians working in blood banks from the southern states of Tamil Nadu and Pondicherry in India. The training program was for 5 days for technicians and 3 days for nurses with theory sessions followed by hands on practical classes regarding the daily activities in blood bank. They were given a pre-evaluation questionnaire to test their knowledge, attitude, and practice followed by a post evaluation questionnaire after conducting the training program. RESULTS: The mean percentage score in the pre evaluation test before the training program for nurses and technicians was 47% and 53% while after the training program; the mean percentage was 66.8% and 77% which was statistically significant in both the groups. The correct blood bank practices followed by nurses and laboratory technicians overall were 67% and 75%, respectively. The technicians and nurses scored poorly in blood bank practices related to hemovigilance. DISCUSSIONS: Regular and standardized training can lead to improvements in the knowledge, skills, and practice of nurses and paramedics who provide blood transfusion services. The constraints faced by the nurses and paramedical personnel needs to be addressed for the overall betterment of blood transfusion services. CONCLUSIONS: The increase in the knowledge subsequently contributed to a better practice in the technicians. The concept of haemovigilance and error reporting has to be stressed on the nurses and paramedics to improve their good practices.